Climate change and macro-financial risks: financial policy responses for an orderly low-carbon transition. (1st March 2023) - D'Orazio, Paola
Abstract: Climate-related financial policies (CRFPs) are needed to tame potential climate-related financial risks deriving from climate change and to finance the low-carbon transition. International engagement levels and CRFP adoption are currently too low to encourage an adequate low-carbon transition and protect the financial system from materializing climate risks. Therefore, greater global commitment is especially important as the COP27 will likely uphold the 1.5 ∘ C targets while following the Intergovernmental Panel on Climate Change's advice to keep global warming below 2 ∘ C. Despite the recent rapid proliferation of the literature on climate-related financial policymaking, some important knowledge gaps remain. Additional investigation, particularly in financial disclosure and stress tests, climate-aligned macro-prudential policies aimed at financial capital, climate data availability, and new research approaches, is required to help decision-makers achieve orderly and swift decarbonization.